2021
DOI: 10.1016/j.bbapap.2021.140693
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of the aggregation propensity of the SARS-CoV-2 proteome: Insight into possible cellular pathologies

Abstract: The coronavirus disease 19 emerged in 2020 is caused by the SARS-CoV-2 virus. The pandemic triggered a turmoil in public health and is having a tremendous social and economic impact around the globe. Upon entry into host cells, the SARS-CoV-2 virus hijacks cellular machineries to produce and maintain its own proteins, spreading the infection. Although the disease is known for prominent respiratory symptoms, accumulating evidence is also demonstrating the involvement of the central nervous system, with possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…The most recent example of which is SARS-CoV-2 and SARS-CoV. Using several computational tools, 10 aggregation-prone proteins in the SARS-CoV-2 reference strain were identified [ 10 ]. The aggregation of these predicted aggregation-prone SARS-CoV-2 proteins, including spike protein peptides, NSP6 protein peptide, ORF10, and NSP1, was confirmed in vitro, and it was also revealed that NSP11 aggregates were toxic to mammalian cells [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent example of which is SARS-CoV-2 and SARS-CoV. Using several computational tools, 10 aggregation-prone proteins in the SARS-CoV-2 reference strain were identified [ 10 ]. The aggregation of these predicted aggregation-prone SARS-CoV-2 proteins, including spike protein peptides, NSP6 protein peptide, ORF10, and NSP1, was confirmed in vitro, and it was also revealed that NSP11 aggregates were toxic to mammalian cells [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear how VP7 aggregation affects AHSV particle assembly or whether the presence of these crystals could contribute to the cellular pathogenesis caused by AHSV infection, which is more severe than that of BTV. Virus protein aggregation has been associated with a range of human diseases such as COVID-19 [ 10 , 11 , 12 , 13 ], hepatitis B [ 14 ], and influenza [ 15 ]. It is, therefore, necessary to identify which forces drive the formation of these crystalline particles to better understand the evolution, pathogenesis, and replication of AHSV.…”
Section: Introductionmentioning
confidence: 99%
“…For example, WGA forms a dimer with eight binding sites for O-GlcNAc, a glycosylation abundant in the FG domains (Li and Kohler, 2014; Schwefel et al, 2010). A recent computational analysis predicted that ORF6 is also aggregate-prone due to the hydrophobic N-terminal region (Flores-Leon et al, 2021). Therefore, we hypothesized that the mechanistic role of the N-terminal region of ORF6 in the nuclear transport inhibition is to mediate aggregation or homo-oligomerization, while its membrane binding is rather coincidental.…”
Section: Resultsmentioning
confidence: 99%
“…A3D can predict the effect of mutations on protein stability and aggregation propensity, as well as suggest solubility-enhancing mutations. This algorithm has been employed to study the constraints imposed by aggregation on protein evolution ( Carija et al , 2019 ), to diagnose the functional impact of genetic mutations ( Seaby and Ennis, 2020 ), to predict the aggregation of the SARS-CoV-2 proteome ( Flores-León et al , 2021 ), to assist the design of novel nanomaterials ( Gil-Garcia and Ventura, 2021 ) or to engineer the solubility of therapeutic proteins ( de Aguiar et al , 2021 ; Gil-Garcia et al , 2018 ) among many other applications.…”
Section: Introductionmentioning
confidence: 99%